Lacunary series in QK type spaces - Jizhen Zhou (Journal of Function Spaces and Applications)
Under mild conditions on the weight function K we characterize lacunary series in QK(p,q) spaces, where QK(p,q) spaces are QK type spaces of functions analytic in the unit disk.